Emulating Prophet Muhammad's Hairstyle As a Form Of Ittiba’ Sunnah By Muslim Youths - Wafa Satria Kamil; Faradelia Mahmudita; Rikana Nur Lailatul Ramadhani; Ahmad Saddad (Al-Shamela : Journal of Quranic and Hadith Studies, 2024)
Appearance is an important thing to be considered by every group. For a man, having a neat hairstyle can give added value to the man. But who would have thought that in Islam there are several hairstyles that are recommended and disgraced in accordance with the teachings of the Prophet SAW. The purpose of this study is to discuss the nature of hair and the way the Prophet combs his hair, as well as the opinion of the Ulama regarding ittaba'. This research uses a type of qualitative research using the library research method or library study analysis. The literature study method is a method of collecting some data obtained from trusted sources or literature, both in the form of hadith master books, journals and websites. The results of this study indicate that the length of the Prophet's hair ranged from reaching both sides of the ear and both shoulders when he did not shave it. The Prophet was not fixated on one state of hair although the most serious state was to leave it short and neat. The Prophet preferred the hairstyle of the Jews and Christians which was left loose. In addition, the Prophet also imitated the hairstyle like the tradition of the polytheists which was split in the middle. This study found that the different lengths of the Prophet's hair mentioned in the hadith are very important to make his hair neat. Therefore, if one wants to follow the Prophet's hair Sunnah, they can shave, comb, or tie their long hair.